AMPLIFIKASI DNA ALGA MERAH (RHODOPHYTA) Eucheuma sp. - Djakatara, Paratiti Dewi; Gerung, Grevo S; Ginting, Elvy L; Sondak, Calvyn F.A.; Rumampuk, Natalie D.C.; Mantiri, Desy M.H. (Sam Ratulangi University, 2018)
Indonesia is a rich source of biodiversity and having a richness species of marine organisms. Indonesia has around 17,000 islands, a suitable place for seaweed growth because of its long coastline. There are around 782 species of seaweed in Indonesia with 196 species of green algae, 134 species of brown algae, and 452 red algae. Any of various seaweeds that potential sources of revenue and mostly can be found around Indonesian waters is Eucheuma sp. including in red algae and can produce carrageenan. Algae Morphological characteristics can be influenced by environmental factors among others: water movement, sunlight, temperature, salinity, and degree of acidity (pH). Beside environmental factors, genetic factors can influence differences in production quality and morphological characteristics of algae. To distinguish morphological characteristics can be analyzed molecularly. In molecular analysis, important steps that must be taken are DNA isolation and genomic DNA amplification. Isolation of red algae DNA in this study using the CTAB method which was modified from Doyle and Doyle (1987), Allen (2006) and Nugroho et al. (2015). Amplification of red algae genomic DNA (Eucheuma sp.) Using COX2 and rbcL genes on PCR. The success of the genomic DNA isolation process and the amplification of COX2 and rbcL genes from Eucheuma sp. detected through UV transilluminator after going through a gel electrophoresis process. Based on this study, several modifications need to be carried out in the DNA isolation stage Eucheuma sp. by using the method of Doyle and Doyle (1987) modifications that need to be carried out include adding vitamin C and liquid nitrogen. Furthermore DNA of Eucheuma sp. successfully amplified by using F-577 and R-753 primers. Indonesia merupakan negara yang kaya akan sumber keanekaragaman hayati dan memiliki kekayaan spesies laut tertinggi. Indonesia memiliki sekitar 17.000 pulau, menjadi tempat yang cocok untuk pertumbuhan rumput laut karena garis pantainya yang panjang. Terdapat sekitar 782 spesies rumput laut di Indonesia dengan 196 spesies alga hijau, 134 spesies alga cokelat, dan 452 alga merah. Salah satu jenis rumput laut yang potensial dan banyak dijumpai di perairan Indonesia adalah Eucheuma sp. yang termasuk dalam alga merah dan dapat menghasilkan karaginan. Karakteristik morfologi alga dapat dipengaruhi oleh faktor lingkungan antara lain : gerakan air, cahaya matahari, suhu, salinitas dan derajat keasaman (pH). Selain faktor lingkungan, faktor genetik dapat mempengaruhi perbedaan kualitas produksi dan karakteristik morfologi pada alga. Untuk membedakan karakteristik morfologi dapat dianalisis secara molekuler. Dalam analisis molekuler, langkah penting yang harus dilakukan adalah isolasi DNA dan amplifikasi DNA genomik. Isolasi DNA alga merah dalam penelitian ini menggunakan metode CTAB yang di modifikasi dari Doyle dan Doyle, (1987), Allen, (2006) dan Nugroho dkk, (2015). Amplifikasi DNA genomik alga merah (Eucheuma sp.) menggunakan gen COX2 dan rbcL pada PCR. Keberhasilan proses isolasi DNA genomik dan amplifikasi gen COX2 dan rbcL dari Eucheuma sp. dideteksi melalui UV transilluminator setelah melalui proses elektroforesis gel. Berdasarkan penelitian ini, beberapa modifikasi perlu dilaksanakan dalam tahap isolasi DNA Eucheuma sp. dengan menggunakan metode Doyle dan Doyle, (1987) modifikasi yang perlu dilaksanakan meliputi penambahan vitamin C dan nitrogen cair. Selanjutnya DNA Eucheuma sp. berhasil diamplifikasi dengan menggunakan primer F-577 dan R-753.